Revitalization Muhammadiyah Youth Movement Trough Anti Corruption Legal Educatioan and Capacity Building in Gubeng District Surabaya City: Revitalisasi Gerakan Pemuda Muhammadiyah dalam Pencegahan dan Pemberantasan Korupsi sebagai Kejahatan Luar Biasa di Kecamatan Gubeng, Kota Surabaya - Wicakasana Prakasa, Satria Unggul; Fatmawati, Ida Nuriya; Saleh , Muhammad Aunurrochim Mas’ad (Jurnal Dedikasi Hukum, 2026)
Corruption as an extraordinary crime not only causes financial losses to the state, but also damages public trust and weakens the quality of public services. This condition requires preventive measures that are not only repressive, but also preventative through strengthening the role of society, especially the younger generation. This community service activity aims to revitalize the role of the Muhammadiyah Youth Force in Gubeng District, Surabaya City, as social supervisors and pioneers of the anti-corruption movement. The methods used are participatory and socio-legal approaches through anti-corruption legal education, training, participatory discussions, and institutional assistance. The results of the activity show an increase in the partners' understanding of the concepts of corruption, maladministration, and public oversight mechanisms as regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001. The results of the activities demonstrated a significant improvement in participants’ legal literacy, analytical abilities, and advocacy skills, particularly in identifying maladministration and potential corrupt practices at the local level. Furthermore, the program produced concrete outcomes that went beyond individual capacity building, including the development of anti-corruption educational modules tailored to local needs, as well as the establishment of a digital advocacy network via social media for integrity campaigns. In addition, a simple community-based reporting mechanism was developed to facilitate public complaints and strengthen accountability in local governance. Thus, this service makes a tangible contribution to raising legal awareness and strengthening youth participation as a preventive strategy in combating corruption at the local level. Thus, this service makes a real contribution to building legal awareness and strengthening youth participation as a preventive strategy in combating corruption at the local level. Abstrak Korupsi sebagai kejahatan luar biasa tidak hanya menyebabkan kerugian finansial bagi negara, tetapi juga merusak kepercayaan publik dan melemahkan kualitas layanan publik. Kondisi ini memerlukan langkah-langkah pencegahan yang tidak hanya bersifat represif, tetapi juga preventif melalui penguatan peran masyarakat, terutama generasi muda. Kegiatan pelayanan masyarakat ini bertujuan untuk mengaktifkan kembali peran Pemuda Muhammadiyah di Kecamatan Gubeng, Kota Surabaya, sebagai pengawas sosial dan pelopor gerakan anti-korupsi. Metode yang digunakan adalah pendekatan partisipatif dan socio-legal melalui pendidikan hukum anti-korupsi, pelatihan, diskusi partisipatif, dan bantuan institusional. Hasil kegiatan menunjukkan peningkatan pemahaman mitra terhadap konsep korupsi, maladministrasi, dan mekanisme pengawasan publik sebagaimana diatur dalam Undang-Undang Nomor 31 Tahun 1999 junto Undang-Undang Nomor 20 Tahun 2001. Hasil kegiatan menunjukkan peningkatan signifikan pada literasi hukum, kemampuan analisis, dan keterampilan advokasi peserta, khususnya dalam mengidentifikasi maladministrasi dan potensi praktik korupsi di tingkat lokal. Lebih lanjut, program ini menghasilkan luaran konkret yang melampaui peningkatan kapasitas individu, tersusunnya modul pendidikan antikorupsi berbasis kebutuhan lokal, serta terbentuknya jejaring advokasi digital melalui media sosial untuk kampanye integritas. Selain itu, dikembangkan pula mekanisme pelaporan berbasis komunitas secara sederhana guna memfasilitasi pengaduan masyarakat dan memperkuat akuntabilitas penyelenggaraan pemerintahan di tingkat lokal. Dengan demikian, layanan ini memberikan kontribusi nyata dalam meningkatkan kesadaran hukum dan memperkuat partisipasi pemuda sebagai strategi pencegahan dalam memberantas korupsi di tingkat lokal.